Chronic DREADD Isn't As Bad As It Sounds. Issue 3 (May 2020) - Hyder, Safwan K.; Forcelli, Patrick A.
Long-Term Chemogenetic Suppression of Spontaneous Seizures in a Mouse Model for Temporal Lobe Epilepsy Desloovere J, Boon P, Larsen LE, et al. Epilepsia. 2019;60(11):2314-2324. doi:10.1111/epi.16368 . Objective: More than one-third of patients with temporal lobe epilepsy (TLE) continue to have seizures despite treatment with antiepileptic drugs, and many experience severe drug-related side effects, illustrating the need for novel therapies. Selective expression of inhibitory Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) allows cell-type-specific reduction of neuronal excitability. In this study, we evaluated the effect of chemogenetic suppression of excitatory pyramidal and granule cell neurons of the sclerotic hippocampus in the intrahippocampal mouse model (IHKA) for TLE. Methods: Intrahippocampal IHKA mice were injected with an adeno-associated viral vector carrying the genes for an inhibitory DREADD hM4Di in the sclerotic hippocampus or control vector. Next, animals were treated systemically with different single doses of clozapine-N-oxide (CNO; 1, 3, and 10 mg/kg) and clozapine (0.03 and 0.1 mg/kg), and the effect on spontaneous hippocampal seizures, hippocampal electroencephalography (EEG) power, fast ripples (FRs), and behavior in the open field test was evaluated. Finally, animals received prolonged treatment with clozapine for 3 days, and the effect on seizures was monitored. Results: Treatment with both CNO and clozapine resulted in a robust suppression of hippocampal seizures for at least 15 hours only in DREADD-expressing animals. Moreover, total EEG power and the number of FRs were significantly reduced. Clozapine-N-oxide and/or clozapine had no effects on interictal hippocampal EEG, seizures, or locomotion/anxiety in the open field test in non-DREADD epileptic IHKA mice. Repeated clozapine treatment every 8 hours for 3 days resulted in almost complete seizure suppression in DREADD animals. Significance: This study shows the potency of chemogenetics to robustly and sustainably suppress spontaneous epileptic seizures and pave the way for an epilepsy therapy in which a systemically administered exogenous drug selectively modulates specific cell types in a seizure network, leading to a potent seizure suppression devoid of the typical drug-related side effects.